The Ontology of the Book Interaction in Literary Genres Under the Review Scale - Rasoul Balavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2021)
This book deals with interaction which is one of the important criticism problems related to literary genres. Interaction is regarded as a perfect standing for literary genres. The researcher Basma Aros tried to examine this idea and Maqāmah and how much this prosimetric literary genre accedes to interactive reading. Choosing Maqamah as a project for this study was a conscious choice because Maqamat is regarded as the basis of the literary genres, and it went beyond other prosimetric literary genres. We chose the book “the Tiger and the Wolf “ written by Sahl Ibn Haroon because it contains conflicting interaction be embodied in an interrelated genre approach. To accomplish this study, the researcher also worked on Maqamat "Badi Al-zamn Al-Hamadzani" and Maqamat "Abi Qasem Al-hariri. According to the descriptive-analytical method, In this critical study, we will focus on the mentioned book to reach some points of conclusion which reveal the rank and importance of this book. Our results show that this book aims at disclosing the secrets of interactive relations among literary genres and their contribution in changing the viewpoint to the genres and their role in the interactive course. In order to show the role of interaction in reading prosaic texts through applying old and modern opinions, the researcher chose the Maqam genre because it includes an exciting genre interaction.